2015
DOI: 10.1002/2015gl064482
|View full text |Cite
|
Sign up to set email alerts
|

A new Eulerian method to estimate “spicy” Agulhas leakage in climate models

Abstract: The Agulhas leakage brings warm and saline water from the Indian Ocean into the South Atlantic, forming part of the returning branch of the global thermohaline circulation, an important component of climate. We develop a new method using the passive tracer spice, to estimate Agulhas leakage transport in an ocean eddy‐resolving climate model that properly captures Agulhas Retroflection and leakage. We identify Agulhas leakage waters as positive spice anomalies (≥ +0.1) and are able to trace leakage to depths gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…This time scale is comparable to the frequency of shedding of Agulhas rings as estimated from observations (Schouten et al 2000). That all hindcast simulations share this common feature (which also comes out when using Putrasahan et al 2015 method, not shown), despite differences in spatial characteristics along Goodhopeline, is a major finding of this study. This suggests that, despite differences in Agulhas rings (size, pathway through Goodhope line, vertical structure), they all represent the dominant mechanism of variability of AL, including the coarser resolution ORCA025 and INDa0.12.…”
Section: Temporal Variability Of Agulhas Leakagesupporting
confidence: 62%
See 4 more Smart Citations
“…This time scale is comparable to the frequency of shedding of Agulhas rings as estimated from observations (Schouten et al 2000). That all hindcast simulations share this common feature (which also comes out when using Putrasahan et al 2015 method, not shown), despite differences in spatial characteristics along Goodhopeline, is a major finding of this study. This suggests that, despite differences in Agulhas rings (size, pathway through Goodhope line, vertical structure), they all represent the dominant mechanism of variability of AL, including the coarser resolution ORCA025 and INDa0.12.…”
Section: Temporal Variability Of Agulhas Leakagesupporting
confidence: 62%
“…When using Putrasahan et al (2015) integration method, this slope increases to −2 , but there is still no change of slope at sub-annual frequencies as observed for the other models. Hence we conclude that AL as a mechanism of variability is not represented in this model.…”
Section: Temporal Variability Of Agulhas Leakagementioning
confidence: 78%
See 3 more Smart Citations